0.5 GHz-1.5 GHz Bandwidth 10W GaN HEMT RF Power Amplifier Design - Shiva Ghandi Isma Ilamaran; Zubaida Yusoff; Jahariah Sampe (Institute of Advanced Engineering and Science, 2018)
With the current development in wireless communication technology, the need for a wide bandwith in RF power amplifier (RF PA) is an essential. In this paper, the design and simulation of 10W GaN HEMT wideband RF PA will be presented. The Source-Pull and Load-Pull technique was used to design the input and output matching network of the RF PA. From the simulation, the RF PA achieved a flat gain between 15dB to 17dB from 0.5GHz to 1.5GHz. At 1.5GHz, the drain efficiency is simulated to achieve 36% at the output power of 40 dBm while the power added efficiency (PAE) was found to be 28.2%.